Offline Promotion Effectiveness in the Digital Era (Case Study of Mican Petshop Sales Promotion and Public Relations) in Attracting Catlovers' Buying Interest) (International Journal of Latest Technology in Engineering Management & Applied Science, 2024)
Abstract: This study describes Mican Petshop's offline promotional strategy to attract cat lovers' interest in buying during 2023. With increasingly fierce competition in the pet industry, Mican Petshop must have an effective promotional strategy. Given the increasing number of competitors in this industry, Mican Petshop feels the need to implement an offline promotional strategy amidst the onslaught of powerful social media to build consumer trust so that they continue to buy products sold in their stores. The type of research used is descriptive qualitative, with the object of research being Mican Petshop's offline promotion in the digital era. The AISAS model is intended to determine consumer behaviour when recommending store products to potential consumers offline. Data was collected in-depth by the store owner and the marketing department. Data analysis was carried out using the Miles and Huberman interactive analysis model. The study results show that the promotional mix that plays an important role in increasing cat lovers' interest in buying at Mican Petshop is sales promotion and public relations. The emphasis on both is due to budget efficiency and customer relationships. Based on the elements of AISAS and a combination of sales promotion and public relations, Mican Petshop can optimize its promotional activities to increase consumer purchasing interest with measurable effectiveness while overcoming challenges that may arise throughout its promotional journey. By focusing on creativity, relevance, and empathetic interaction with consumers, Mican Petshop can continue to increase the effectiveness of its promotions. This is proven by the sales target that has been met. Mican Petshop still survives without promotion through social media because of business partners' experience of content plagiarism and the nature of advertising, which amplifies expressiveness.